2005
DOI: 10.1081/pdt-200054429
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of a Lyophilized Formulation of BMS-204352: Identification of Degradants and Role of Elastomeric Closures

Abstract: The purpose of this study was to identify two degradation products formed in the parenteral lyophilized formulation of BMS-204352, investigate the possible role of elastomeric closures in their formation, and develop a strategy to minimize/control their formation. The first degradant was identified as the hydroxymethyl derivative (formaldehyde adduct, BMS-215842) of the drug substance formed by the reaction of BMS-204352 with formaldehyde. Structure confirmation was based on liquid chromatography/mass spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To date, no identification studies of E/L have compared ion trap and QTOF mass detection. In the articles included in this meta-synthesis, the identification of E/L with only ion trap detection coupled to LC was successful in one study out of four [18,23,25,28]. Petrusevski et al successfully identified two E/L (Irganox 1010 and Irgafos 168) with an ion trap mass detector [18].…”
Section: Comparison Of Qtof With Ion Trap Mass Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no identification studies of E/L have compared ion trap and QTOF mass detection. In the articles included in this meta-synthesis, the identification of E/L with only ion trap detection coupled to LC was successful in one study out of four [18,23,25,28]. Petrusevski et al successfully identified two E/L (Irganox 1010 and Irgafos 168) with an ion trap mass detector [18].…”
Section: Comparison Of Qtof With Ion Trap Mass Detectionmentioning
confidence: 99%
“…Petrusevski et al successfully identified two E/L (Irganox 1010 and Irgafos 168) with an ion trap mass detector [18]. In the three other articles using ion trap detection, the identification of E/L was possible by using other techniques such as nuclear magnetic resonance (NMR), Fourier-transform infrared spectroscopy, and GC/MS [23,25,28].…”
Section: Comparison Of Qtof With Ion Trap Mass Detectionmentioning
confidence: 99%